Az igazságügyi szakértői tevékenység az állami szerepvállalás tükrében - Halmosné Siket, Zsuzsanna (Debreceni Jogi Műhely, 2016)
This is an essay about the connection between the judicial experts and the public sector. The expert opinion has a special role in the system of the envindeces in the criminal procedure. The expert opinion as a kind of evidence has a short history in the criminal procedure, because this evidence is the product of the new age. The second difference from the other evidences that the judicial expert needs a special quality, and because of this cause the law rules controls who has premitted to become expert and make expert opinion. The Criminal Procedure Act controls when should and when must delegate a judicial expert the criminal procedure. Consequently the state has a main role in connection with the activity of the experts by the law rules.In the first part I show the short history of the appearance of the expert opinion in the criminal procedure.In the second part I show the main law rules in connection with the judicial experts, and I write about the expert chambers, the list of experts, and the professional institutes and corporations.The third part is about the fees and taxes in connection with the judicial experts. In this part I show the problems about who have to pay the fees in the end of the criminal procedure. The acitvity of the judicial expert is always expensive, so the expeneses can grow quickly. If the accused is acquited the expense will stay in encumbrance of the state, and if the accused is convicted, the accused will have to pay the expenses. So this expenses are enourmous encumbrances for everyone. This problem has waited solution yet. Reduction of  costs or hunting out  justice ?  Sometimes very hard to decide, which one is the better. The judicial experts also work in the private sector. The competition of the judicial experts is big in the private sector, and this phenomenon is influences the private prices.The end of the essay is a summary which contains my main conclusions.